Eficiencia operativa y gestión financiera en la empresa KOZUE HOGAR SAC de Iquitos periodo 2024 - Saucedo Abad, Jhonny (2025)
The objective of this research was to determine how operational efficiency and financial management are related in the company KOZUE HOGAR SAC in Iquitos during the 2024 period. The study followed a quantitative approach with a non-experimental research design, a cross-sectional design type, and a correlational scope. A total of 35 employees from KOZUE HOGAR SAC participated in the study. The findings revealed a considerable positive correlation between operational efficiency and financial management, with a Pearson correlation coefficient of 0.862. This indicates that improving the company's operations directly impacts its ability to manage finances effectively. Additionally, operational efficiency and financial planning were found to be strongly correlated, also with a Pearson correlation coefficient of 0.862. This suggests that better operational management enables more precise and robust financial planning. Furthermore, the relationship between operational efficiency and risk management, although moderate with a Pearson correlation coefficient of 0.533, remains significant. This implies that optimizing operations can contribute to an improved ability to identify and mitigate financial risks. Overall, the results demonstrate that operational efficiency is a key factor in the financial stability of KOZUE HOGAR SAC. Enhancing it allows for better planning, budgeting, treasury management, and risk management, ultimately generating a positive impact on the company's overall performance.